SOCIOECONOMIC AS STUNTING PREDICTOR ON CHILDREN AGED 24-59 MONTHS AT BEFORE AND DURING COVID-19 PANDEMIC: Sosial Ekonomi sebagai Prediktor Stunting pada Anak Usia 24-59 Bulan Sebelum dan Selama Pandemi COVID-19 - Sri Suryani Wahyuningrum; Slamet Riyanto; Taufiq Hidayat; Hadi Ashar (Universitas Airlangga, 2023)
Background: Stunting is a high-priority malnutrition problem globally. The COVID-19 pandemic was predicted to increase hunger and worsen the condition of stunted children. Purpose: To determine the socioeconomic factors for stunting in children aged 24-59 months before and during the COVID-19 pandemic in the Magelang Regency. Methods: This study used a case-control design from August to November 2021. Subjects were children under five aged 24-59 months from the Magelang Regency. The subjects consisted of 162 stunted children and 166 normal children. The nutritional status screening was derived from e-PPGBM data, and was further validated through repeated anthropometric measurements. Phone interviews with mothers or trustees were done to obtain primary data. Data were analyzed using a chi-square test and declared significant if the p-value was below 0.05. Results: Socioeconomic status factors significantly related to stunting before the COVID-19 pandemic were family income below the region's minimum wage (cOR = 2.18; 95% CI = 1.31-3.64), incapability to fulfill food and household needs (cOR = 2; 95% CI = 1.25-3.23), and incapability to save income (cOR = 2; 95% CI = 1.32-3.33). During the COVID-19 pandemic, a socioeconomic factor that was found to be significantly related to stunting was incapability to fulfill food and household needs (cOR = 1.57; 95% CI = 1-2.46). Conclusion: Low family income and incapability to fulfill food and household needs was strongly associated with stunting. Improvements to community empowerment and stunting prevention programs in response to COVID-19 need to be made to prevent new stunting cases.